Effectiveness of School-Based Integrated Mental Health and Substance Use Prevention Programs for Adolescents: A Systematic Review and Meta-Analysis - Jihye Shin; Kyung-Young Hong (Behavioral Sciences, 2026)
School-based prevention programs increasingly incorporate mental health-related components to prevent substance use among adolescents. This study aimed to evaluate the effectiveness of integrated school-based mental health and substance use prevention programs for adolescents through a systematic review and meta-analysis. A systematic literature search was conducted across 12 electronic databases for studies published between January 2016 and April 2026. Randomized controlled trials (RCTs) and cluster randomized controlled trials evaluating school-based integrated prevention programs for adolescents were included. Random-effects meta-analyses were performed for substance-use outcomes, including alcohol-related outcomes and binge drinking, using pooled odds ratios (ORs) and 95% confidence intervals (CIs). Mental health and psychosocial outcomes were synthesized narratively because heterogeneity in outcome definitions, measurement instruments, and assessment periods precluded meaningful quantitative pooling. A total of 16 reports representing 10 independent trials were included in the systematic review, and five independent trial comparisons were included in the primary meta-analysis. Integrated prevention programs significantly reduced alcohol-related behaviors among adolescents compared to control groups (OR = 0.56, 95% CI = 0.37–0.86, p = 0.008). Significant preventive effects were also observed for binge drinking outcomes (OR = 0.32, 95% CI = 0.16–0.64, p = 0.001). Most interventions incorporated emotional regulation, resilience enhancement, coping skills, stress management, and help-seeking promotion. Digital and online approaches were frequently used. Narrative findings suggested potential benefits for selected psychosocial and mental health-related outcomes; however, these outcomes were not quantitatively pooled and were not consistently sustained across follow-up periods. Integrated school-based prevention programs incorporating mental health-related components demonstrated beneficial effects on alcohol-related behaviors and binge drinking among adolescents. Evidence regarding mental health and psychosocial outcomes was based on narrative synthesis and remains less conclusive. These findings support the importance of integrated prevention approaches that simultaneously address substance use and mental health in school settings. However, additional large-scale RCTs with standardized outcome measures and long-term follow-up are needed to strengthen the current evidence base.